Perbedaan Kepuasan Perawat dalam Pendokumentasian Asuhan Keperawatan Berbasis Komputerisasi dan Manual (Studi di RS Paru dan RS Baladhika Husada Kabupaten Jember) (The Different of Nursing Satisfaction by Computerized Nursing Documentation and Manual Nurs - Yunita Selly Santoso; Dodi Wijaya; Retno Purwandari (UPT Percetakan dan Penerbitan Universitas Jember, 2018)
Nursing documentation is the important thing that must be done by a nurse. There are two kind ofnursing documentation, computerized nursing documentation and manual nursing documentation.This research purposes to find out the different of nursing satisfaction by computerized nursingdocumentation and manual nursing documentation. Crosssectional design was used in thisresearch. Sampling technique used simple random sampling. Total of sample was 30 respondentsand devided by 2 groups who used computerized nursing documentation and who used manualnursing documentation. Data was analyzed by Mann Whitney. The result showed nurse who usedcomputerized nursing documentation have very satisfactied category (100%). Nurse who usedmanual nursing documentation have very satisfactied category (100%). The result of statisticanalyze showed that p Value (1.000)>alpha (0.05), that means there wasn’t differences of nursingsatisfaction by computerized nursing documentation and manual nursing documentation (study inParu Hospital and Baladhika Husada Hospital Subdistrict at Jember). The reason why nursingsatisfaction by manual nursing documentation have very satisfactied category, because it couldease in used of than computerized nursing documentation.Keywords: computerized nursing documentation, manual nursing documentation, satisfaction